Frailty and Quality of Life After Cochlear Implantation in Older Adults. (20th April 2021) - Aylward, Alana; Murphy‐Meyers, Morganne; Allen, Chelsea McCarty; Patel, Neil S.; Gurgel, Richard K.
Abstract : Objective: To examine the relationship among frailty index, hearing measures, and hearing‐related quality of life (QOL) in older recipients of cochlear implants. Study Design: Cross‐sectional survey. Setting: Academic medical center. Methods: Adults aged ≥65 years at the time of receiving cochlear implants between July 13, 2000, and April 3, 2019, were asked to complete a questionnaire on hearing‐related QOL. Chart review was performed to identify patients' characteristics. Correlations were calculated between frailty index and audiologic outcome measures as well as between speech recognition scores and QOL scores. Linear regression models were developed to examine the impact of clinical characteristics, frailty index, and hearing measures on hearing‐related QOL. Results: Data for 143 respondents were included. The mean age was 80.7 years (SD, 7.1), with a mean 27.8 years of hearing loss (SD, 17.4) before implantation. The mean frailty index was 11.1 (SD, 10.6), indicating that patients had 1 or 2 of the measured comorbidities on average. No correlation was found between lower frailty index (better health) and hearing scores, including pure tone averages (PTAs) and speech recognition scores. Lower frailty index and larger improvement in PTA after cochlear implantation predicted better QOL scores on univariate analysis (respectively, P =. 002, β = −0.42 [95% CI, −0.68 to −0.16]; P =. 008, β = −0.15 [95% CI, −0.26 to −0.04]) and multivariate analysis ( P =. 047, β = −0.28 [95% CI, −0.55 to −0.01]; P =. 006, β = −0.16 [95% CI, −0.28 to −0.05]). No speech recognition scores correlated with QOL after cochlear implantation. Conclusions: Frailty index does not correlate with hearing scores after cochlear implantation in older adults. Lower frailty index and more improvement in PTA predict better QOL scores after cochlear implantation in older adults.